Fuzzy neutrosophic Soft Ideal Theory Fuzzy neutrosophic Soft Local Function and Generated Fuzzy neutrosophic Soft Topological Spaces - Ather Farhan lafta; Dr. Mohammed J. Al-Mesafer; Dr. Ayed E. Hashoosh (University of Thi-Qar Journal, 2019)
The purpose of this paper is to introduce the notion of fuzzy neutrosophic soft ideal in fuzzy neutrosophic soft set theory. The concept of fuzzy neutrosophic soft local function is also introduced. These concepts are discussed with a view to find new fuzzy neutrosophic soft topologies from the original one. The basic structure, especially a basis for such generated fuzzy neutrosophic soft topologies also studied here. Finally, the notion of compatibility of fuzzy neutrosophic soft ideals with fuzzy neutrosophic soft topologies is introduced and some equivalent conditions concerning this topic are established here